The Myth of the Winter Olympics in Sarajevo in Bosnian Collective Memory - Rekść, Magdalena (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
The 14th Winter Olympics, held from February 8 to 19, 1984, still evoke nostalgic memories of the inhabitants of Bosnia and Herzegovina, especially its capital. Although it was Yugoslavia’s declining moment, the communist authorities put much effort into promoting the atmosphere of “brotherhood and unity.” However, soon after, the war broke out, and the post-war shape of the Bosnian state lead to the permanent political, social and economic crisis. As a result, Serbs, Croats and Bosniaks cannot agree about shared history and common heroes. One of the few crossing points is the myth of the 14th Winter Olympic Games: possibly these days sport idols (Jure Franko, Katarina Witt, Jayne Torvill and Christopher Dean) can fill the gaps in almost empty Bosnian symbolic apparatus.